Analysis of Students' Mathematical Representation Skills through Android Application-based Mathematics Learning - Yuliardi, Ricki; Juandi, Dadang; Maizora, Syafdi; Mahpudin, Asep (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
This research is motivated by the low mathematical representation skills of students. This is evidenced by the mathematics learning achievement of Indonesian students in TIMSS and PISA which has not moved from the bottom 10 ranks. In learning mathematics, there are still some obstacles, including students who are still difficult to read mathematical expressions, errors in principles and procedures, not being able to connect one concept to another and difficulty communicating mathematical ideas / ideas. Mathematics learning based on android applications is an alternative idea that can be a solution to the problems above. This study aims to examine: (1) How is the application of Android-based mathematics learning (2) How is the process of mathematical representation and student responses in the application of Android-based mathematics learning. (3) How to anticipate learning that must be perfected to optimize student representation skills. This research method uses qualitative methods using instruments in the form of teacher observation sheets, student observation sheets, interview sheets and student understanding tests.Penelitian ini dilatarbelakangi oleh masih rendahnya keterampilan representasi matematis siswa. Hal ini dibuktikan dengan prestasi belajar matematika siswa Indonesia pada TIMSS dan PISA masih belum beranjak dari 10Ã‚Â  peringkat terbawah. Di dalam pembelajaran matematika, masih ditemukan beberapa kendala diantaranya siswa masih sulit membaca ekspresi matematika, kesalahan prinsip dan prosedur, belum mampu menghubungkan antara satu konsep dengan konsep lainnya serta kesulitan dalam mengkomunikasikan gagasan/ide matematika. Pembelajaran matematika berbasis aplikasi android adalah salah satu gagasan alternatif yang dapat menjadi solusi permasalahan diatas. Penelitian ini bertujuan untuk mengkaji : (1) Bagaimanakah penerapan pembelajaran matematika berbasis Android(2) Bagaimanakah proses representasi matematis dan respon siswa dalam penerapan pembelajaran matematika berbasis Android. (3) Bagaimana antisipasi pembelajaran yang harus disempurnakan untuk mengoptimalkan keterampilan representasi siswa. Metode penelitian ini menggunakan metode kualitatif dengan menggunakan instrumen berupa lembar observasi guru, lembar observasi siswa, lembar wawancara dan tes pemahaman siswa.